The Dynamics of Beneficiaries’ Experiences in Social Protection Policies: A Hermeneutic Phenomenological Approach - Wirata , Gede; Lubis , Mukhlis; Widyaningsih , H.; Veithzal , Andria Permata; Wardana , Ali (Journal of Posthumanism, 2025)
Social protection policies serve as crucial instruments in reducing social inequality and enhancing the well-being of vulnerable communities. However, in practice, beneficiaries often face administrative challenges, digital disparities, and varying perceptions of the policy’s effectiveness. This study employs a hermeneutic phenomenological approach to explore the subjective experiences of beneficiaries in accessing and utilizing social assistance. Data were collected through in-depth interviews and participatory observations, then analyzed using Interpretative Phenomenological Analysis (IPA) to identify key themes that reflect their experiences. The findings reveal that complex bureaucratic procedures and a lack of policy dissemination lead many beneficiaries to encounter difficulties in obtaining assistance. While the digitalization of social protection systems aims to improve efficiency, it inadvertently creates access gaps for individuals with low digital literacy. Furthermore, beneficiaries perceive social assistance not only as economic support but also as recognition of their condition by the government, despite lingering feelings of insufficiency in the long term. These findings highlight the need for administrative reforms to ensure greater inclusivity, user-oriented digital access improvements, and policy development based on the real-life experiences of beneficiaries. This study offers critical insights for policymakers in designing more effective, responsive, and sustainable social protection programs in response to evolving social and economic dynamics.